Dysferlin Mediates the Cytoprotective Effects of TRAF2 Following Myocardial Ischemia Reperfusion Injury. Issue 1 (26th February 2014) - Tzeng, Huei‐Ping; Evans, Sarah; Gao, Feng; Chambers, Kari; Topkara, Veli K.; Sivasubramanian, Natarajan; Barger, Philip M.; Mann, Douglas L.
Abstract : Background: We have demonstrated that tumor necrosis factor (TNF) receptor‐associated factor 2 (TRAF2), a scaffolding protein common to TNF receptors 1 and 2, confers cytoprotection in the heart. However, the mechanisms for the cytoprotective effects of TRAF2 are not known. Methods/Results: Mice with cardiac‐restricted overexpression of low levels of TRAF2 (MHC‐TRAF2LC ) and a dominant negative TRAF2 (MHC‐TRAF2DN ) were subjected to ischemia (30‐minute) reperfusion (60‐minute) injury (I/R), using a Langendorff apparatus. MHC‐TRAF2LC mice were protected against I/R injury as shown by a significant ≈27% greater left ventricular (LV) developed pressure after I/R, whereas mice with impaired TRAF2 signaling had a significantly ≈38% lower LV developed pressure, a ≈41% greater creatine kinase (CK) release, and ≈52% greater Evans blue dye uptake after I/R, compared to LM. Transcriptional profiling of MHC‐TRAF2LC and MHC‐TRAF2DN mice identified a calcium‐triggered exocytotic membrane repair protein, dysferlin, as a potential cytoprotective gene responsible for the cytoprotective effects of TRAF2. Mice lacking dysferlin had a significant ≈39% lower LV developed pressure, a ≈20% greater CK release, and ≈29% greater Evans blue dye uptake after I/R, compared to wild‐type mice, thus phenocopying the response to tissue injury in the MHC‐TRAF2DN mice. Moreover, breeding MHC‐TRAF2LC onto a dysferlin‐null background significantly attenuated the cytoprotective effects of TRAF2 after I/R injury. Conclusion: The study shows that dysferlin, a calcium‐triggered exocytotic membrane repair protein, is required for the cytoprotective effects of TRAF2‐mediated signaling after I/R injury.